The video guides and social tagging with the methodology of video annotation - Ruiz-Rey, Francisco José; Pérez-Galán, Rafael; Cebrián-Robles, Violeta; Cebrián-de-la-Serna, Manuel (My University, 2020)
Teaching guides are mandatory for quality agencies to evaluate teaching programmes, just as institutions require teachers to comply with them. This teaching resource has been seen as a very effective tool for the information and orientation of students in university programmes. However, the reality may turn out to be different, as the current practices with these guides are often not the desirable ones, as they are not used, read and studied by students with the level of depth that teachers wish, and in some cases they may be a mere formality for students, thus losing all their potential and meaning. The communication we present aims to present the results of a teaching innovation project to break this problem by producing video guides as digital resources that are more motivating for students. In addition, to design and experiment with a new methodology for its application and analysis of these resources in teaching programmes of any kind (face-to-face, blended and online programmes) by means of multimedia annotations. In this work we present the objectives, methodologies and resources proposed in this project, as the main conclusions we have reached as it has been to check a greater participation in the understanding of the programmes by the students, as a more active and motivating methodology to work with these resources in the classroom for an online modality
Producto del PIE Video guías docentes
Keywords: Enseñanza - Innovaciones; Enseñanza - Evaluación; Recursos en Internet; Vídeo en la enseñanza; Educational innovation; Digital resources; Online courses; Social tagging; Teaching guides; Video annotation